Biodecolorization of Remazol Brilliant Blue–R dye by Tropical White-Rot Fungi and Their Enzymes in The Presence of Guaiacol - Sita Heris Anita (Department of Chemistry, Faculty of Mathematics and Natural Sciences, Universitas Andalas, 2021)
The ability of the tropical white-rot fungi and their enzyme to decolorize synthetic dyes was investigated. Production of lignin-modifying enzymes (LMEs) from the three new isolated fungi, namely Trametes hirsuta D7, Ceriporia sp. BIOM 3, and Cymatoderma dendriticum WM01 were observed for 9 days incubation under static condition. The results showed that the LMEs production enhanced in the present of guaiacol. T. hirsuta D7 produced only laccase (Lac), with the highest activity was 22.6 U/L on the 5th-day of the cultivation. At the same time, Ceriporia sp. BIOM 3 and C. dendriticum WM01 secreted both laccases (Lac) with the activities 0.2 U/L and 1.0 U/L, respectively, and manganese peroxidase (MnP) with the activities 0.1 U/L and 1.0 U/L, respectively. Among the fungi, T. hirsuta D7 efficiently degraded 65% Remazol Brilliant Blue–R (RBBR) dye within 72 h using the only laccase. This study shows that laccase may have a major role in synthetic dyes' decolorization process, followed by MnP and LiP.